View of the temple on the Galitzinberg - Prixner, Gottfried, 1746-1819 (engraver):::Creator::::::::::::; Weidmann, F. C. (Franz Carl), 1787-1867 (author):::Contributor:::::::::::: (R. Sammer; Austria; Vienna, 2015)
Engraving of the temple at the Galitzinberg, with two pages of explanatory text.